Gastric electrical stimulation improves symptoms and need for supplemental nutrition in children with severe nausea and vomiting: A ten‐year experience. Issue 9 (15th June 2021) - Orsagh‐Yentis, Danielle K.; Ryan, Kelsey; Hurwitz, Nicole; Diefenbach, Karen A.; Teich, Steven; Mousa, Hayat; Bali, Neetu; Vaz, Karla; Yacob, Desale; Di Lorenzo, Carlo; Lu, Peter L.
Abstract: Background: Gastric electrical stimulation (GES) is a promising therapy for children with severe nausea and vomiting, but information on long‐term outcomes is limited. We sought to evaluate the long‐term efficacy and safety of GES and to describe patient benefit and satisfaction. Methods: Using a prospective registry, we identified patients aged <21 years treated with GES at our institution between 2009 and 2019. Encounters were selected at baseline prior to GES and at follow‐up at 1 month, 12 months, and the most recent visit. We compared symptoms, route of nutrition, and medication usage at baseline to follow‐up timepoints. Factors associated with improvement were evaluated. We recorded complications and need for battery replacement. We contacted families to administer the Glasgow Children's Benefit Inventory (GCBI) and a parent satisfaction questionnaire. Key Results: Eighty‐five patients (68.2% female, median age 15.8 years) completed a trial of temporary GES due to severe nausea and vomiting. Seventy‐seven (90.6%) had a positive response and underwent permanent stimulator placement. Use of tube feeding or parenteral nutrition (PN) decreased from 72.7% at baseline to 29.9% at the most recent follow‐up ( p < 0.001). Higher baseline vomiting severity was associated with the ability to stop supplemental nutrition by 1 month ( p < 0.05). Fourteen patients (18.2%) had complications, primarily due to stimulator‐associated discomfort, and 29 (37.7%) required battery replacement. Median GCBI was +52.1, indicating health‐related benefit. Conclusions and Inferences: Children with severe nausea and vomiting treated with GES experienced significant and durable improvement in symptom severity and their ability to tolerate oral nutrition. Abstract : Children with severe nausea and vomiting treated with gastric electrical stimulation experienced significant improvement in their symptoms and ability to tolerate oral nutrition. The use of tube feeding and parenteral nutrition decreased from 73% at baseline to 30% at the most recent follow‐up. *denotes p < 0.05, ** p < 0.01, *** p < 0.001 when compared to baseline.